Is Poor Sleep Quality Associated With Greater Disability in Patients With Multiple Sclerosis?. Issue 2 (4th March 2018) - Vitkova, Marianna; Gdovinova, Zuzana; Rosenberger, Jaroslav; Szilasiova, Jarmila; Mikula, Pavol; Stewart, Roy E.; Groothoff, Johan W.; van Dijk, Jitse P.
Abstract : Poor sleep is a serious burden for patients with multiple sclerosis (MS). The aim of this study is to assess whether the association between sleep quality and disability in MS patients is direct or mediated by depression, pain, and fatigue. We collected data from 152 patients with MS who filled out the Pittsburgh Sleep Quality Index, the Hospital Anxiety and Depression Scale, the Multidimensional Fatigue Inventory and one item of the Short Form-36 regarding pain. The relationship between poor sleep and disability was found to be indirect, mediated by depression ( p < 0.05), pain ( p < 0.001) and physical fatigue ( p < 0.01). Treatment of sleep disturbances may have beneficial effects beyond improving sleep. It may reduce depression, pain, and physical fatigue, which in turn may lessen disability.